Gender and locational dimensions of shocks on household welfare: empirical evidence from Nigeria. Issue 5 (4th July 2018) - Boniface Ajefu, Joseph
ABSTRACT: Many households in developing countries are exposed to numerous adverse events. The absence of a complete market for insurance and imperfect risk-sharing among households can lead to a significant effect on household welfare from shocks. This article examines the heterogeneous effects of income shocks on household welfare using two waves of the Nigerian General Household Survey Panel datasets from 2010/11 and 2012/13. The study adopted the household fixed effects approach, and the results show that households in the top quintile experienced an increased consumption expenditure compared to those in the bottom quintile in terms of rainfall distribution. There are also heterogeneous effects of income shocks on the gender and locational characteristics of the households.